Rethinking a (still) ongoing debate on the Covid-19 pandemic. The withdrawal of the mandatory use of face masks on public transport - Ortiz Fernández, Manuel (EUNOMÍA. Revista en Cultura de la Legalidad, 2023)
In the context of the Covid-19 pandemic, several provisions were adopted that, in practice, suspended (or limited) citizens’ fundamental rights. As a result, the health emergency situation caused the declaration of the second state of alarm since the approval of the Spanish Constitution. However, although the debates seem to be over, the abolition of the mandatory use of a mask on public transport has shown that there are still questions to offer a legal answer. Therefore, in this study, we will analyze the legal authorization (state, regional and local) to clarify the adequacy of the decision above.